Targeting myotonic dystrophy by preimplantation genetic diagnosis-karyomapping - Cheng-Wei Wang; Yung-Liang Liu; Chi-Huang Chen (Elsevier, 2019)
Objective: To report a case with Myotonic dystrophy type I with successful preimplantation genetic diagnosis-karyomapping. Case report: A 34-year-old female carrier of myotonic dystrophy type I was treated at our clinic with a successful pregnancy after preimplantation genetic testing for monogenic disorders using karyomapping of her blastocysts. Conclusion: Myotonic dystrophy type I is an inherited autosomal dominant disease producing various neuromuscular disturbances. Offspring of carriers have a 50% chance of carrying CTG repeat sequences in the DMPK gene, and various time-consuming methodologies have been developed for genetic diagnosis. With a novel, efficient, and precise method by karyomapping using single nucleotide polymorphism arrays to diagnose single gene disorders, one could terminate the transmission of single gene disorder. Herein, we reported a 34-year-old female carrier of myotonic dystrophy type I achieve a successful pregnancy after preimplantation genetic testing for monogenic disorders using karyomapping method of her blastocysts. Keywords: Karyomapping, Myotonic dystrophy, Preimplantation genetic testing